The role of institutionalized cooperation in transboundary basins in mitigating conflict potential over hydropower dams - Schmeier, Susanne (Frontiers in Climate, 2024)
Numerous dams are currently being built, many of them in transboundary basins. This can lead to disagreements and conflicts between riparian states, compromising not only environmental and social sustainability, but also regional stability and peace. Addressing such conflict risks, states have developed legal and governance mechanisms to address the conflict potential around dams, ranging from international water law principles to dam-specific provisions in basin treaties and from basin management plans to environmental impact assessment approaches. The paper assesses those from a global and a case study perspective. It finds that mechanisms for preventing or mitigating conflicts over dams, mainly by mitigating their impacts on neighbouring countries, remain underdeveloped, especially in those basins currently facing rapid dam development. However, where they exist and function effectively, they can significantly reduce conflict risks compared to a nonmechanism-counterfactual and thus protect riparian ecosystems, people and countries.